Atrial Fibrillation Ablation During Hospitalization for Acute Heart Failure: Feasibility and Role of Pulsed Field Ablation - Marek, Josef; Stojadinović, Predrag; Wichterle, Dan; Peichl, Petr; Hašková, Jana; Borišincová, Eva; Štiavnický, Petr; Čihák, Robert; Šramko, Marek; Kautzner, Josef (Journal of cardiovascular electrophysiology, 2025)
INTRODUCTION: Atrial fibrillation (AF) can cause or aggravate heart failure (HF). Catheter ablation (CA) is an effective treatment for AF. This study focused on the feasibility and outcomes of emergent AF ablation performed during hospitalization for acute HF. METHODS AND RESULTS: We retrospectively investigated patients who underwent emergent CA for AF during hospitalization for acute HF in 2018-2024. Arrhythmia recurrence was the primary endpoint. The combination of arrhythmia recurrence, HF hospitalization, and all-cause death was the secondary endpoint. Patients were censored 1 year after the index procedure. We included 46 patients, 35% females, with median age of 67 [interquartile rage: 61, 72] years and left ventricular ejection fraction (LVEF) of 25 [23, 28]%. Thermal CA was performed in 14 patients, and pulsed field ablation (PFA) in 32 patients. Procedure time was significantly shorter with PFA compared to thermal CA (77 [57, 91] vs. 166 [142, 200] minutes, p < 0.001). Fluoroscopy time was longer with PFA (9.5 [7.6, 12.0] vs. 3.9 [2.9, 6.0] minutes, p < 0.001), with a borderline trend towards higher radiation dose (75 [53, 170] vs. 50 [30, 94] μGy.m2, p = 0.056). Extrapulmonary ablation was frequent (86% and 84% for thermal CA and PFA, p > 0.9). The estimated freedom from the primary endpoint was 79% after PFA and 64% after thermal CA (p = 0.44). The estimated freedom from the secondary endpoint was 76% after PFA and 57% after thermal CA (p = 0.43). LVEF improved by 24% ± 2% (p < 0.001) in patients with the first manifestation of HF and by 14% ± 4% (p = .004) in patients with decompensated HF diagnosed earlier. CONCLUSIONS: Emergent CA of AF during acute HF hospitalization is safe and associated with improved LVEF and good clinical outcomes. In the PFA era, the rate of these procedures is progressively increasing as they are readily available and easy to perform compared to thermal ablation.
Keywords: Heart Failure; Middle Aged; Stroke Volume; lidé středního věku; Ventricular Function, Left; Atrial Fibrillation; Heart Rate; Treatment Outcome; mužské pohlaví; výsledek terapie; catheter ablation; pulsed field ablation; recidiva; časové faktory; hospitalizace; Humans; senioři; Retrospective Studies; Hospitalization; tepový objem; akutní nemoc; Patient Admission; lidé; fibrilace síní; Risk Factors; acute heart failure; electroporation; Acute Disease; rizikové faktory; obnova funkce; Female; thermal ablation; Feasibility Studies; atrial fibrillation; funkce levé komory srdeční; Aged; retrospektivní studie; Time Factors; Recovery of Function; srdeční selhání; ženské pohlaví; katetrizační ablace; příjem pacientů; Male; Action Potentials; akční potenciály; srdeční frekvence; Recurrence; posterior wall isolation; Catheter Ablation; studie proveditelnosti